A Review of the Biotechnological Production of Methacrylic Acid - Lebeau, Juliana; Efromson, John P.; Lynch, Michael D. (Frontiers in Bioengineering and Biotechnology, 2020)
Industrial biotechnology can lead to new routes and potentially to more sustainable production of numerous chemicals. We review the potential of biobased routes from sugars to the large volume commodity, methacrylic acid, involving fermentation based bioprocesses. We cover the key progress over the past decade on direct and indirect fermentation based routes to methacrylic acid including both academic as well as patent literature. Finally, we take a critical look at the potential of biobased routes to methacrylic acid in comparison with both incumbent as well as newer greener petrochemical based processes.